The Turkish Adaptation of the Student Satisfaction and Self-Confidence in Learning Scale Used in Simulation Education - Karaçay, Pelin; Kaya, Hatice (Florence nightingale journal of nursing, 2017)
Aim: The aim of this study is to determine the reliability and validity of the Turkish version of the “Student Satisfaction and Self Confidence in Learning” scale published by the National League for Nursing. Method: This methodological study was conducted in two stages. In the first stage, the language adaptation of the scale to Turkish was performed via back-translation. To evaluate content validity, the scale was reviewed by nursing faculty members who were experts in simulation education. The content validity index was calculated based on these experts’ opinions. In the second stage, the reliability of the scale was evaluated. From June to November 2015, 120 nursing students who had previous experience with simulation volunteered to participate in the study. t this stage, test-retest reliability, Cronbach’s alpha coefficient and item-total correlations were evaluated. The construct validity of the scale was done using confirmatory factor analysis. Results: The content validity index of the Turkish version of the scale was appropriate (CVI= 0.87). fter modification, it was found that the model was a good fit. Cronbach’s lpha coefficient was 0.88. Removal of item 13 would have improved alpha to 0.90. test-retest intraclass correlation coefficient was 0.50. Conclusion: The results of this study determined that the Turkish version of the “Student Satisfaction and Self Confidence in Learning Scale” was valid and reliable and could be used in nursing research and practice in Turkey.